2021
DOI: 10.3389/fphar.2021.775271
|View full text |Cite
|
Sign up to set email alerts
|

The Na+/Ca2+ Exchanger 3 Is Functionally Coupled With the NaV1.6 Voltage-Gated Channel and Promotes an Endoplasmic Reticulum Ca2+ Refilling in a Transgenic Model of Alzheimer’s Disease

Abstract: The remodelling of neuronal ionic homeostasis by altered channels and transporters is a critical feature of the Alzheimer’s disease (AD) pathogenesis. Different reports converge on the concept that the Na+/Ca2+ exchanger (NCX), as one of the main regulators of Na+ and Ca2+ concentrations and signalling, could exert a neuroprotective role in AD. The activity of NCX has been found to be increased in AD brains, where it seemed to correlate with an increased neuronal survival. Moreover, the enhancement of the NCX3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Moreover, it should be noted that the remodeling of neuronal ionic homeostasis by altered ion channels and transporters is a pivotal characteristic of AD pathogenesis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be noted that the remodeling of neuronal ionic homeostasis by altered ion channels and transporters is a pivotal characteristic of AD pathogenesis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of ER Ca 2+ homeostasis resulting in a drop of luminal Ca 2+ is a hallmark of ER stress in chronic disease. Upregulation of rNCX to promote ER refilling, by a mechanism similar to that described in Figure 2 , has recently been shown to protect primary neurons against ER stress and death in a mouse model of Alzheimer’s disease [ 35 ]. It is expected that future research of this nature on animal models, combined with physical-chemical experiments and stochastic simulations will lead to a better understanding of the mechanism whereby the components of the Ca 2+ signaling units, or nano-junctions, interact in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we have recently reported about the occurrence of an ER Ca 2+ remodeling in the Tg2576 primary neurons. In particular, we showed that the enhanced activity of the Na + /Ca 2+ exchanger 3 promotes an increased ER Ca 2+ refilling in Tg2576 neurons in comparison with WT neurons [ 47 ]. Moreover, we demonstrated that the I A -mediating K V 3.4 channel subunit, which is overexpressed and functionally upregulated in Tg2576 reactive astrocytes, regulates astrocytic [Ca 2+ ] i transients and ER Ca 2+ levels [ 52 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from embryonic brain tissues was isolated by salt precipitation as previously described [ 47 ]. Briefly, embryonic brain tissues were harvested during cerebral dissection and then thawed and homogenized with the TRI-reagent (Sigma-Aldrich, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%